Voltage Stability Enhancement of Distribution System Using Network Reconfiguration in the Presence Of DG - Murthy, G.V.K; Sivanagaraju, S.; Satyanarayana, S.; Hanumantharao, B. (Distributed Generation & Alternative Energy Journal, 2015)
Voltage stability improvement is an important issue in power system planning and operation. This article presents the effect of re- configuration in the presence of distributed generation (DG) in radial distribution system to improve the voltage stability with different load models by using Artificial Bee Colony (ABC) algorithm. The analysis is accomplished using a voltage stability index which can be evaluated at each node of the distribution system. The network reconfiguration involves a mechanism for selection of the best set of branches to be opened, one from each loop, such that the reconfigured radial distribu - tion system possesses desired performance characteristics. The location of DG has the main effect of voltage stability on the system. Simulation study is conducted on 69-bus radial test system to verify the efficacy of the proposed method.